Diminutives: Exceptions to Harmonic Uniformity - Péter Rebrus (Universitat Autònoma de Barcelona, 2016)
Front-back harmony in Hungarian is governed by the root of words: it disregards suffixes in most cases. That is, a back-vowelled root (B) followed by any number of neutral-vowelled suffixes (N) will take a back-vowelled suffix (B+N+N+B), but a root with a back vowel followed by several neutral vowels is possibly followed by a front-vowelled suffix (F): BNN+F/B. We call this Harmonic Uniformity. This is respected even in truncated stems: NB→N+N+B, although NN stems practically never take a back suffix (NN+F). Diminutive forms are the only exceptions to this pattern. We claim that this is so, because diminutive forms are much more loosely related to their “base” than is the case with any other types of suffixation.